Employee Performance and Work Motivation: The Impact of Transformational and Transactional Leadership Mediator - Sudarmadi, Muhammad Azmi Syauqirrahman; Santosa, Perdana Wahyu (SAN Scientific, 2025)
This study investigates the effects of transformational and transactional leadership on employee performance, with work motivation acting as a mediating variable. Conducted at The Acacia Hotel Jakarta, a four-star hotel established on June 21, 1996, the research involved 60 employees. A quantitative approach was used, utilizing questionnaires distributed to all employees through purposive sampling. Data analysis was conducted using WarpPLS Partial Least Square Structural Equation Modeling (PLS-SEM). The findings revealed that transactional leadership positively influences employee performance, while transformational leadership negatively impacts it. Moreover, transactional leadership negatively affects work motivation, whereas transformational leadership has a positive influence on it. Interestingly, work motivation does not significantly affect employee performance and does not mediate the relationship between either leadership style and employee performance. These results suggest that while transactional leadership can drive performance directly, it may reduce motivation. On the other hand, transformational leadership boosts motivation but may not translate into improved performance. This highlights a critical consideration for managers in balancing leadership styles to enhance both motivation and performance. Understanding the complex dynamics between leadership, motivation, and performance can help organizations formulate more effective management strategies.